THE LABORATORY SPECIFICITY OF THE EVALUATION TEST DEFINITIONS - Akhmedova Dilyona Bakhtiyor kizi; Rustamova Rahbarxon (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
However, for the practical physician who is trying to answer questions about the possibility of haemorrhagic complications during surgical interventions, about the cause of bleeding that has already occurred, or about the intensity of intravascular coagulation and the presence of DIC syndrome, as well as about the effectiveness of antithrombotic therapy, the number of laboratory tests is limited to a much smaller number. In this regard, we have subdivided all laboratory tests, with the help of which the state of haemocoagulation is investigated, into several groups depending on the questions posed to the doctor [4,5,6,7,8].